A phenomenographic study of British civil servants' conceptions of accountability - Lupson, Jonathan (Cranfield University, 2007)
In the United Kingdom civil servants have traditionally been accountable to their managerial and political superiors for probity and due process in the execution of their duties. Recent parliamentary and administrative reforms have changed this view. Individual civil servants are now additionally accountable to a range of external groups for the results of their work. This change is reflected in the role of Senior Responsible Owner (SRO), a civil servant accountable to a management team for the achievement of a predefined project outcome. This thesis challenges the idea that accountability is a unitary concept that can be defined by others and delegated in this way. The subjective nature of human understanding suggests theoretical grounds for the existence of different conceptions of accountability among different individuals for a given outcome. In this research I have applied the analytical approach known as phenomenography to the study of these different conceptions. The approach has been widely used, mainly in fields outside management, to establish the bounded number of qualitatively different ways in which a given aspect of reality is conceived by different individuals. Analysis of interviews with 30 SROs from 12 government departments revealed four different conceptions of accountability, each with multiple attributes. The conceptions can be arranged in a hierarchy of increasing richness and complexity. This research contributes to theoretical knowledge of the concept of accountability in the field of public administration in four ways. First, the study adds time to the known attributes of accountability. Second, the study confirms sanctions as an attribute of accountability. Third, the hierarchy of four conceptions of accountability throws new light on the subject that calls into question the unitary view. Fourth, the results refute the notion of a schismogenic paradox of accountability and provide empirical support for meanings of accountability that transcend this paradox.